Inhibitory effects of extracellular self‐DNA: a general biological process?. Issue 1 (28th January 2015) - Mazzoleni, Stefano; Cartenì, Fabrizio; Bonanomi, Giuliano; Senatore, Mauro; Termolino, Pasquale; Giannino, Francesco; Incerti, Guido; Rietkerk, Max; Lanzotti, Virginia; Chiusano, Maria Luisa
Summary Self‐inhibition of growth has been observed in different organisms, but an underlying common mechanism has not been proposed so far. Recently, extracellular DNA (exDNA) has been reported as species‐specific growth inhibitor in plants and proposed as an explanation of negative plant–soil feedback. In this work the effect of exDNA was tested on different species to assess the occurrence of such inhibition in organisms other than plants. Bioassays were performed on six species of different taxonomic groups, including bacteria, fungi, algae, plants, protozoa and insects. Treatments consisted in the addition to the growth substrate of conspecific and heterologous DNA at different concentration levels. Results showed that treatments with conspecific DNA always produced a concentration dependent growth inhibition, which instead was not observed in the case of heterologous DNA. Reported evidence suggests the generality of the observed phenomenon which opens new perspectives in the context of self‐inhibition processes. Moreover, the existence of a general species‐specific biological effect of exDNA raises interesting questions on its possible involvement in self‐recognition mechanisms. Further investigation at molecular level will be required to unravel the specific functioning of the observed inhibitory effects.